2010
DOI: 10.1172/jci44721
|View full text |Cite
|
Sign up to set email alerts
|

In obesity and weight loss, all roads lead to the mighty macrophage

Abstract: Obesity is associated with infiltration of white adipose tissue (WAT) by macrophages, which contributes to the development of insulin resistance. In this issue of the JCI, Kosteli and colleagues demonstrate that weight loss is unexpectedly also associated with rapid, albeit transient, recruitment of macrophages to WAT and that this appears to be related to lipolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
(20 reference statements)
2
30
0
Order By: Relevance
“…Adipose tissue macrophages (ATMs) are classified into classical activated macrophages (also known as M1 macrophages) and alternatively activated macrophages (also known as M2 macrophages). It is well known that M1 macrophages infiltration of WAT triggers inflammation, while M2 macrophages suppress inflammation4546. Obviously, purified EPS administration induced the M2 macrophages and inhibited M1 macrophages in adipose tissue and liver, which explained the improved inflammation status by EPS.…”
Section: Discussionmentioning
confidence: 90%
“…Adipose tissue macrophages (ATMs) are classified into classical activated macrophages (also known as M1 macrophages) and alternatively activated macrophages (also known as M2 macrophages). It is well known that M1 macrophages infiltration of WAT triggers inflammation, while M2 macrophages suppress inflammation4546. Obviously, purified EPS administration induced the M2 macrophages and inhibited M1 macrophages in adipose tissue and liver, which explained the improved inflammation status by EPS.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies suggested that macrophage recruitment to adipose tissue is a normal response that associates with activation of adipocyte lipolysis during the early phase of weight loss and fasting ( 8,23 ). However, the metabolic factors that induce ATM infi ltration during lipolysis are still undefi ned.…”
Section: Discussionmentioning
confidence: 99%
“…We extend these observations by demonstrating that exogenous administration of TNF-␣ can impair function in eWAT arteries from NC-, but not HF-fed, mice and that the chronic in vivo exposure of eWAT arteries to elevated TNF-␣ resulting from HF feeding underlies the observed endothelial dysfunction. Although the causal role of adipose tissue dysfunction and inflammation in obesity-associated metabolic and cardiovascular disease risk is well established (3,15,24,32), there is surprisingly little information regarding the role of vascular function per se in the overall function/phenotype of the adipose tissue (30), or how this vascular function is affected by obesity (12). Here, we provide direct evidence for a HF-diet-mediated, TNF-␣-induced, impairment in adipose tissue arterial function that may have important implications for tissue-specific and systemic metabolic and vascular health.…”
Section: Discussionmentioning
confidence: 99%